The Association Between Muslim Religiosity and Internet Addiction Among Young Adult College Students - Nadeem, Mohammad (Journal of religion and health, 2019)
The major focus of this research was to investigate the effects of religiosity factor on internet addiction among young adults enrolled at college level. We adopted two instruments to gather the information including OK-religious attitude scale for Muslims developed and used by Ok, Uzeyir, and Internet Addiction Test prepared by Widyanto and McMurran. In total, 800 Muslim college students enrolled in four colleges at graduate level of southern Punjab Pakistan were chosen through multi-phase sampling. The subscales revealed more than .76 Cronbach alpha coefficients. The outcomes expressed positive role in case of DE conversion in world faith toward internet indications, whereas intrinsic religious orientations remained beneficial in decreasing internet usage. Students' anti-religion subscale demonstrates higher increase in becoming of internet addict; however, intrinsic religious orientations show significant decrease in using internet. Similarly, DE conversion in world faith view and Anti-Religion Scale indicate students' significant contributions in expecting them being internet addict. The study determines that the religiosity factor considerably illuminate the variances in developing internet addiction among the Muslim college adults with the direct effect of intrinsic religious orientation and indirect effect of anti-religion aspect.